A Framework for Monitoring Cargo Movement using Virtual Reality - Mantovani, Carlo Smaniotto; Pavanatto, Leonardo; Pinho, Márcio Sarroglia (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2023)
This research focuses on developing an architecture for monitoring the location and status of entities within a real-world environment and representing this in a virtual or augmented reality environment. The primary objective was to create an application that enables real-time monitoring of cargo movement in a port setting, demonstrating this architecture. By establishing communication with a server storing entity data, accurate information display and updates are ensured. The research presents a preliminary project that showcases the feasibility of the proposed architecture, demonstrating the connection between the application and server to display updated data in a VR environment. Results indicate successful real-time synchronization and data exchange, highlighting the benefits of such an architecture in enhancing logistics operations and providing a comprehensive understanding of entity movement. This research sets the foundation for future endeavors in creating large-scale virtual environments and exploring different communication frameworks, expanding the potential of VR technology in diverse monitoring scenarios.